Designing Mode Learning based PMRI-STEM Approach using the Coffee Grinder Context for Culinary Arts Vocational High School Students - Novi Susanti; Ratu Ilma Indra Putri; Nyimas Aisyah; Hartono Hartono (Journal of Honai Math, 2026)
Learning mode as one of the measures of central tendency is often limited to identifying the value that appears most frequently without understanding its meaning in real-world situations. Students tend to understand mode procedurally but experience difficulties in interpreting it as a representation of majority preference in contextual decision-making. Therefore, this study aims to design mode learning based on the PMRI-STEM approach using the context of coffee grinder use to support students’ conceptual understanding of mode in Culinary Arts Vocational High School. This study employed a design research approach consisting of preliminary design, teaching experiment, and retrospective analysis. The participants were 25 students in Grade 10 Culinary Arts Vocational High School. Data were collected through classroom observations, students’ worksheets, interviews, and learning documentation, then analyzed descriptively to examine students’ learning processes during PMRI-STEM learning activities. The study resulted in a learning trajectory consisting of activities involving adjusting grinder machine settings, grinding coffee beans with different grind sizes, observing brewing characteristics, organizing preference data into frequency tables, and determining the mode as the most frequently chosen grind size. The findings showed that students were able to identify the mode correctly and interpret it as a representation of majority customer preference used for determining standard coffee shop menu settings. Students also developed contextual reasoning by connecting grinder settings, brewing results, data representation, and statistical decision-making. These findings indicate that PMRI-STEM learning using the context of coffee grinders can support students’ understanding of mode and contextual statistical literacy in vocational mathematics learning.